2004
DOI: 10.1093/nar/gkh515
|View full text |Cite
|
Sign up to set email alerts
|

Energetic basis for selective recognition of T{middle dot}G mismatched base pairs in DNA by imidazole-rich polyamides

Abstract: To complement available structure and binding results and to develop a detailed understanding of the basis for selective molecular recognition of T.G mismatches in DNA by imidazole containing polyamides, a full thermodynamic profile for formation of the T.G-polyamide complex has been determined. The amide-linked heterocycles f-ImImIm and f-PyImIm (where f is formamido group, Im is imidazole and Py is pyrrole) were studied by using biosensor-surface plasmon resonance (SPR) and isothermal titration calorimetry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 48 publications
5
19
0
Order By: Relevance
“…The general finding that f-ImPyIm binds to these sequences with positive cooperativity is not surprising, according to previous work. DNA molecules with high GC content often have a wide (0.5–0.6 nm) minor groove (11), in which two polyamide molecules can readily stack without significant widening of the minor groove (16,27,2931). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general finding that f-ImPyIm binds to these sequences with positive cooperativity is not surprising, according to previous work. DNA molecules with high GC content often have a wide (0.5–0.6 nm) minor groove (11), in which two polyamide molecules can readily stack without significant widening of the minor groove (16,27,2931). …”
Section: Resultsmentioning
confidence: 99%
“…SPR experiments were performed using either a BIACORE 2000 or 3000 instrument (Biacore AB) as described previously with the DNA hairpins shown in Figure 2B (15,16,27,29). Steady state and kinetic data were analyzed as described previously (16).…”
Section: Methodsmentioning
confidence: 99%
“…Aich and Dasgupta (8) have shown that the association equilibrium constant ( K a ) of Mith bound to calf thymus DNA is ∼1.15 × 10 5 M −1 in the presence of Mg(II). The recent development of biosensor technologies for biospecific interaction analysis enables monitoring of a variety of molecular reactions in real-time using SPR (36,37). In this study, we demonstrate that molecular interactions between DNA-binding drug (Mith) and biotinylated target DNA probes immobilized on sensor chips is detectable by SPR technology using a commercially available biosensor.…”
Section: Discussionmentioning
confidence: 99%
“…The structural and thermodynamic parameters of this binding were thoroughly determined. [17] This class of agents is important due to the high biological significance of the TG mismatch, [18] which also represents a particularly hard target for recognition by small molecules because it is only slightly less stable than the Watson-Crick base pairs. [19] Over the past few years, we have shown that a macrocyclic bisacridine compound (BisA, Scheme 1) recognizes base-pairing defects, like abasic sites [20] and thymine-containing mismatches, [21] through a putative threading bisintercalation mode.…”
Section: Introductionmentioning
confidence: 99%